The quantification and improvement of vehicle support capacity in a weak soil - Shorten, David (Cranfield University, 2004)
The aim of this study was to improve the characteristics of surfacing methods/materials for the temporary support of military vehicles travelling over weak soils. Both off road travel and poor existing road networks provide problems for vehicle mobility in military operations under these conditions. Conventional road construction materials are often in short supply and engineered solutions such as Class 30 & 70 Trackway are expensive and form a significant logistical burden on the military supply chain. In this situation the use of locally available alternative materials in the construction of temporary roads can reduce the time taken to get routes operational, allowing the tempo of operations to be maintained. The work reported focussed on two main areas of work, namely: i) The development of a technique for assessing the soil support capacity in the form of a flat plate (45 x 30 mm) penetrometer to aid the decision/ planning process when faced with poor soil support, and ii) the evaluation of the relative performance of a range of alternative materials/ techniques in laboratory conditions at 1/5'*’ scale and full size. The results of load-sinkage tests of a family of plate sizes indicate that by normalising the data with respect to plate width a common relationship existed for all plate sizes in each of the soil conditions investigated. From this, a technique was developed to estimate the load support of a plate with dimensions equivalent to the contact patch of a tyre using load-sinkage data from a small plate penetrometer, allowing estimates of: i) sinkage or rut depth expected from a vehicle load, and ii) the load at a sinkage equivalent to the tyre contact patch width, a point at which the vehicles were assumed to be immobilised. Comparison between the rut depth of a single pass of a towed wheel and the sinkage from plate tests (45 x 30 mm) were within 20% in a sandy loam soil of bulk unit weight 12.2 and 13.4 kN/m^. Load sinkage predictions of a 450 x 300 mm plate from a small plate penetrometer were within 35% in a sandy loam soil with bulk unit weights of 11.7 and 13.4 kN/m^. Load sinkage predictions for a very weak sandy loam (11.3 kN/m^) and loose sand (15.1 - 16.1 kN/m^) soils tended to be significantly underestimated especially at large plate sizes, mainly due to scaling effects in these David Shorten, 2004 Cranfield University, Silsoe 11 situations as well as the significant re-arranging occurring in weak soil subjected to loaded plates. Improvements in accuracy to 25-35% could be made in these conditions by increasing the size of the plate penetrometer to 90 x 60 mm and utilising a similitude scaling technique. Materials/techniques for improving soil support have been classified into 4 categories, namely: sheet materials, rigid members, aggregate materials and stabilisation techniques. The use of sheet materials, in this case a Hessian geotextile, proved effective in improving the in situ soil support; it was possible to optimise the width and placement depth to increase load support by a factor of 1.8. A folded confinement technique encapsulating a soil fill was developed further, resulting in a 3-fold improvement in the load support. Tied corduroy techniques performed best with a 5- fold improvement in load support. Factors such as the rope tension between members were found to be important to produce a stable road surface. The performance of aggregates increased with larger aggregate sizes. Increasing the thickness of the aggregate layer enhanced load support in stone aggregate, while in wood and rubber aggregate performance is affected by the initial compressibility of the material. Aggregate mixed with a sand filler proved effective at reducing the compressibility of the alternative aggregate materials, thus enhancing performance. The use of alternative materials in military operations has been identified as very scenario dependent. Alternative materials have been shown to increase the load support capability of weak soils. Although alternative materials are unlikely to be used as a substitute in conventional road construction, their use on short sections of roadway is feasible. Situations where conventional aggregate materials are limited and an alternative aggregate can be obtained locally would offer a solution enabling military operations to continue. Significant quantities of materials are required to construct even small sections of roadway in weak soil conditions; success is very much dependent on the amount of material locally available, for example a 100 m section may require 180 m^ of timber aggregate approximately equal to 0.25 ha of a 45 yr Sitka Spruce plantation. This information will be of use to aid decisions made by the Combat Engineer and has been recommended by the MOD for inclusion in the Military Engineering Volume.